Skin-friendly double-gel-system cataplasm matrix capable of being rapidly cured and formed and preparation method thereof
By adopting a double gel system in the babu agent, using specific component combinations and process flow, the problems of excessive curing and molding of the babu agent and poor skin permeability are solved, and rapid curing and high permeability of the babu agent are achieved. Preparation, suitable for industrial continuous production.
Patent Information
- Application Number
- CN202411316277.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-03
AI Technical Summary
The curing and forming time of existing babu agents is too long during the preparation process, which affects continuous industrial production and has poor skin permeability.
Using a hydrophilic lipophilic double gel system, including oil gel and hydrogel phase, the combination of components and process flow in a specific proportion can achieve rapid curing and forming, including monoglyceride, ethyl cellulose, and volatile oils of traditional Chinese medicine. , carrageenan, polyvinylpyrrolidone, gelatin, glycerin, sodium polyacrylate, kaolin and other components are mixed and cured by means of thermal emulsification and stirring.
It realizes rapid curing and molding of babu agent, shortens preparation time, improves skin permeability and stability, is suitable for industrial continuous production, and has good gel mechanical properties and no sensitization.
Smart Images

Figure BDA0005052311040000251
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of pharmaceutical preparations, and in particular relates to a skin-friendly, rapidly curable double-gel system cataplasm matrix and a preparation method thereof. Background Art
[0002] Babu is a good topical preparation, which is mainly prepared by mixing drugs, medicinal material extracts and suitable hydrophilic matrix and then coating them on the backing material, and then preparing them through processes such as refining, coating, and shearing. Modern Babu mostly appears in the form of a single hydrogel system, but the skin permeability of the hydrogel system is poor, so it is less effective in delivering hydrophobic substances. The double gel system is prepared by mixing the incompatible hydrogel and oil gel phases in different proportions through shearing. It has the advantages of both phases and shows better performance than a single gel: delivering hydrophilic and lipophilic substances, easy to prepare, cooling and moisturizing effects, good spreadability, easy to wash, better skin affinity, improving the permeability of drugs to the skin, better stability at room temperature, and the properties of the system can be adjusted by adjusting the ratio of the two phases.
[0003] At the same time, modern poultices also have another disadvantage. Generally, the curing time during the preparation process is too long, which affects subsequent cutting and packaging processes.
[0004] The invention patent with publication number CN103961415 discloses a Tianjiu Babu preparation and a preparation method thereof. The Babu preparation needs to be coated, covered with a film, with the backing facing upward, left to cure for 12-36 hours, and then cut and packaged.
[0005] The invention patent with publication number CN114681552 discloses a musk pain-relieving papuam and a preparation method thereof. The papuam needs to be coated and left to stand for 24 hours before slicing.
[0006] The invention patent with publication number CN114983983 discloses an improved cataplasm and its application. The cataplasm needs to be coated with an applicator, covered with a lining cloth, and matured overnight in an indoor environment at a room temperature of 20-30°C and a relative humidity of 20-50% to obtain the product.
[0007] The invention patent with publication number CN104258067 discloses a pharmaceutical composition for a cataplasm, a cataplasm and a preparation process thereof. The cataplasm needs to be coated on a non-woven fabric, dried in an oven at 40-60°C, cut and packaged.
[0008] The above invention patents all require a long time of curing and molding after coating or require additional operations, such as heating and drying to extend the curing time, which increases the preparation time or process and is not conducive to industrial continuous production. Summary of the invention
[0009] In order to solve the above technical problems, the present invention provides a skin-friendly and rapidly curable double gel system cataplasm matrix, which has good affinity for the skin, is comfortable to use, and has good permeability; at the same time, it cures and forms quickly, shortens the preparation time and reduces the process, and is suitable for industrial continuous production. Another object of the present invention is to provide a method for preparing the above cataplasm matrix.
[0010] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a skin-friendly and quickly curable double-gel system patch agent matrix, wherein the double-gel system patch agent matrix includes an oil gel system and a hydrogel system; the oil gel system includes monoglyceride, ethyl cellulose, and volatile oil of traditional Chinese medicine; the hydrogel system includes a first phase and a second phase; the first phase includes a toughening component A, a toughening component B, purified water, a cross-linking regulator, and an antibacterial agent; the second phase includes glycerol, sodium polyacrylate, and kaolin; the toughening component A includes any one of carrageenan and konjac glucomannan or a combination of two of them; the toughening component B includes any one of polyvinyl pyrrolidone and gelatin or a combination of two of them.
[0011] As a preferred embodiment of the above technical solution, the double gel system cataplasm matrix includes, by weight, 0.30-2.50 parts of monoglyceride, 1.00-5.00 parts of ethyl cellulose, 6.00-18.00 parts of volatile oil of traditional Chinese medicine, 0.10-0.50 parts of toughening component A, 1.00-10.00 parts of toughening component B, 12.00-48.00 parts of purified water, 0.00-0.20 parts of cross-linking regulator, 0.10-0.50 parts of antibacterial agent, 20.00-40.00 parts of glycerol, 14.00-30.00 parts of sodium polyacrylate, and 3.00-22.00 parts of kaolin.
[0012] As a preferred embodiment of the above technical solution, the Chinese medicine volatile oil includes three categories: pungent and warm, pungent and cool, and pungent and hot, specifically including any one or more of peppermint oil, cinnamon oil, dried ginger oil, evodia rutaecarpa oil, clove oil, schizonepeta oil, and atractylodes oil.
[0013] As a preferred embodiment of the above technical solution, the polyvinyl pyrrolidone includes one of polyvinyl pyrrolidone K30 and polyvinyl pyrrolidone K90, or a combination of the two.
[0014] As a preferred embodiment of the above technical solution, the cross-linking regulator includes any one of citric acid, tartaric acid, lactic acid, malic acid, and disodium ethylenediaminetetraacetate, or a combination of more than one of them.
[0015] As a preferred embodiment of the above technical solution, the antibacterial agent includes any one or more combinations of potassium sorbate, chitin, chitosan, protamine, and tea polyphenols.
[0016] As a preferred embodiment of the above technical solution, the double gel system cataplasm matrix includes, by weight, 0.30-1.00 parts of monoglyceride, 1.50-3.50 parts of ethyl cellulose, 8.00-13.00 parts of Chinese medicine volatile oil, 0.10-0.35 parts of toughening component A, 2.00-8.00 parts of toughening component B, 24.00-37.00 parts of purified water, 0.00-0.10 parts of cross-linking regulator, 0.10-0.35 parts of antibacterial agent, 28.00-38.00 parts of glycerin, 15.00-26.00 parts of sodium polyacrylate, and 5.00-16.00 parts of kaolin.
[0017] The preparation method of a skin-friendly, fast-curing dual-gel system poultice matrix comprises the following steps: stirring and mixing monoglyceride, ethyl cellulose and Chinese herbal volatile oil, and obtaining an oil gel system after heat emulsification; adding an appropriate amount of purified water to swell toughening component A, toughening component B, a cross-linking regulator and an antibacterial agent, and then heating and stirring to dissolve to prepare a solution to obtain a first phase; stirring and dissolving glycerol, sodium polyacrylate and kaolin at room temperature to prepare a second phase; mixing the oil gel, the first phase and the second phase at the same time, rapidly heating and stirring to mix evenly, coating them on a substrate, and then cutting and packaging to obtain the product.
[0018] As a preferred embodiment of the above technical solution, the monoglyceride, ethyl cellulose and Chinese medicine volatile oil are stirred and mixed at a speed of 600-1200r / min, and the temperature of thermal emulsification is 70-100°C; the toughening component A, the toughening component B, the cross-linking regulator and the antibacterial agent are swollen with purified water and then heated and stirred at 40-60°C to dissolve and prepare a solution to obtain the first phase; the oil gel, the first phase and the second phase are heated and stirred at 40-60°C to mix.
[0019] The present invention uses monoglyceride and ethyl cellulose as the oil gel in the oil gel system, and adopts a combination of low molecular weight and high molecular weight oil gel to better improve the stability of the oil gel; at the same time, the present invention uses Chinese herbal volatile oil as the oil phase in the oil gel system, and the pungent Chinese herbal volatile oil can increase the permeability of the skin after acting on the skin, that is, open the skin pores and promote drug absorption. The weight ratio of the oil gel system to the hydrogel system in the present invention is 1:9-2:8. If the ratio is too high, oil seepage occurs; if the ratio is too low, the mechanical properties of the gel deteriorate.
[0020] In the present invention, carrageenan and konjac glucomannan are selected as toughening component A. Glucomannan and carrageenan have a strong gel synergistic effect. When mixed with carrageenan, the greater the proportion of glucomannan, the stronger the gel toughness; on the contrary, the more brittle the gel. Therefore, the weight ratio of carrageenan to konjac glucomannan in the present invention is 5:5-6:4.
[0021] In the present invention, polyvinyl pyrrolidone and gelatin are selected as toughening component B. The freezing force value of gelatin in the present invention is 200-260. If the freezing force value is too low, the overall solidification time of the cataplasm is prolonged, the jelly strength is low, and it is easy to spoil; if the freezing force value is too high, the overall solidification time of the cataplasm is too fast, which is not convenient for subsequent addition. In the present invention, the weight ratio of polyvinyl pyrrolidone to gelatin is 2:8-3:7. The proportion of polyvinyl pyrrolidone should not be too high, which will weaken the solidification effect of gelatin.
[0022] In the present invention, one of citric acid, tartaric acid, lactic acid, malic acid and disodium ethylenediaminetetraacetic acid is selected as a cross-linking regulator, i.e., a pH regulator. The amount of the cross-linking regulator added in the present invention should be adjusted according to the overall pH value of the poultice, combined with the pH tolerance of human skin, to increase skin affinity and maintain pH = 7-8.5.
[0023] In the present invention, natural organic preservatives are selected as antibacterial agents, which have the advantages of strong antibacterial properties, safety and non-toxicity, good water solubility, good thermal stability, and a wide range of effects. At the same time, the skin affinity and storage stability of the poultice are further improved.
[0024] In the present invention, glycerin is selected as a humectant, firstly to adjust the viscosity, ductility and moisturizing properties of the poultice; secondly, to act as a solvent to facilitate the dispersion, swelling and dissolution of the adhesive and cross-linked main substance therein.
[0025] In the present invention, sodium polyacrylate is selected as the cross-linking skeleton to play a supporting role in the overall framework of the matrix. The molecular weight of sodium polyacrylate in the present invention is 1×10 6 -9×10 7 If the molecular weight is too low, it will mainly play a thickening role, which will lead to poor overall strength of the matrix and easy breakage when stretched; if the molecular weight is too high, it will mainly be used as a water absorbent, which will cause the hydrogen bonds on the sodium polyacrylate chain segments to combine with water during the mixing stage, thereby forming a hydration layer, and the overall viscosity will increase, and there will be no time for uniform mixing.
[0026] In the present invention, kaolin is selected as a cross-linking agent. The weight ratio of kaolin to sodium polyacrylate in the present invention is 3:10-2:5, which can maintain an appropriate cross-linking speed and significantly improve the curing time. If the ratio is too low, the cross-linking is too slow, which prolongs the curing time. At the same time, the surface of the cataplasm is sticky and has a poor hand feel, which affects the skin fit; if the ratio is too high, the cross-linking is too fast, the rapid curing, the stirring and mixing are limited, and the drug coating is too strong, thereby affecting the drug release.
[0027] After selecting the matrix raw materials and dosage, consider the subsequent process conditions. For example, the stirring time and speed. The stirring time should not be too long and the stirring speed should not be too high, which will cause the overall viscosity of the matrix to decrease. The most influencing factor is sodium polyacrylate. For heating temperature, like gelatin, too high or too low heating temperature will prolong the gel time. The reaction of sodium polyacrylate and kaolin, plus the cross-linking regulator can accelerate the gelation of the reaction. In the hydrogel system, it is divided into two major items in advance and stirred separately, that is, the order of adding each component is to mix the toughening component A, toughening component B, purified water, cross-linking regulator, and antibacterial agent into one phase, and then mix the cross-linking skeleton, cross-linking agent, and moisturizer into one phase. The cataplasm matrix made in this order is easy to stir evenly, has better viscoelasticity, and is soft and easy to apply.
[0028] The skin-friendly and fast curable double gel system cataplasm matrix of the present invention has the following advantages:
[0029] 1. High skin affinity, no allergenicity, good adhesion: the matrix is mainly water-in-oil type, water is used for moisturizing, oil is used for nourishing, no allergic or irritating reaction to the skin, no pain or residue when peeling, and can be peeled off repeatedly;
[0030] 2. Fast curing and molding: Rapid molding shortens the preparation time and reduces the process;
[0031] 3. Strong skin permeability: The dual gel system is easier to deliver hydrophilic and lipophilic drugs through the skin;
[0032] 4. Good stability: The dual gel system has stronger adaptability to the environment and can maintain stable performance under a wider temperature range and humidity conditions, thereby extending the service life;
[0033] 5. Excellent mechanical properties of the gel: On the one hand, the two network structures in the double gel interact with each other to form an "interlocking" effect, which enhances the mechanical strength of the gel; on the other hand, due to the synergistic effect between the toughening components, its gel strength is also increased.
[0034] In summary, the skin-friendly, rapidly curable dual-gel system cataplasm matrix of the present invention can meet the requirements of industrial continuous production, has moderate adhesion, is non-irritating and non-allergenic to the skin, improves skin permeability, has stable quality, and has good gel mechanical properties. It can be used to prepare various traditional Chinese medicine cataplasms and is easy to use and promote. DETAILED DESCRIPTION
[0035] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Example 1
[0037] Monoglyceride: 0.54g;
[0038] Ethyl cellulose: 2.45 g;
[0039] Peppermint oil: 9.60g;
[0040] Carrageenan: 0.10g;
[0041] Konjac glucomannan: 0.10g;
[0042] Polyvinylpyrrolidone (PVP-K30): 1.08 g;
[0043] Gelatin (freezing strength value: 230): 2.52g;
[0044] Tartaric acid: 0.00g;
[0045] Potassium sorbate: 0.10g;
[0046] Purified water: 30.00g;
[0047] Glycerol: 36.00g;
[0048] Sodium polyacrylate (molecular weight: 4×10 6 ): 22.00g;
[0049] Kaolin: 8.30g.
[0050] 1. Preparation of oil gel system
[0051] 1.1. Mix 0.54 g monoglyceride, 2.45 g ethyl cellulose and 9.60 g peppermint oil, add them at 800 r / min, and heat emulsify at 70°C for 40 min to obtain an oil gel;
[0052] 2. Preparation of hydrogel system
[0053] 2.1. Add 30.00 g purified water to 0.10 g carrageenan, 0.10 g konjac glucomannan, 1.08 g polyvinyl pyrrolidone, 2.52 g gelatin, 0.00 g tartaric acid, and 0.10 g potassium sorbate, and then heat and stir at 60° C. for 40 min to dissolve and prepare a solution to obtain the first phase;
[0054] 2.2. Dissolve 36.00 g of glycerol, 22.00 g of sodium polyacrylate and 8.30 g of kaolin at room temperature and stir for 10 min to obtain the second phase;
[0055] 3. Mix
[0056] 3.1. Add the first phase and second phase of the oil gel and hydrogel at the same time, heat and stir at 60℃ for 10 minutes to mix evenly, then apply, cut and package.
[0057] Example 2
[0058] Monoglyceride: 0.33g;
[0059] Ethyl cellulose: 1.50 g;
[0060] Cinnamon oil: 8.00g;
[0061] Carrageenan: 0.08g;
[0062] Konjac glucomannan: 0.06g;
[0063] Polyvinylpyrrolidone (PVP-K90): 1.79 g;
[0064] Gelatin (freezing strength value: 250): 5.11g;
[0065] Citric acid: 0.05g;
[0066] Chitosan: 0.12 g;
[0067] Purified water: 24.00g;
[0068] Glycerol: 30.00g;
[0069] Sodium polyacrylate (molecular weight: 9×10 6 ): 23.00g;
[0070] Kaolin: 9.00 g;
[0071] 1. Preparation of oil gel system
[0072] 1.1. Mix 0.33 g monoglyceride, 1.50 g ethyl cellulose and 8.00 g cinnamon oil, add at 900 r / min, and heat emulsify at 90 ° C for 30 min to obtain an oil gel;
[0073] 2. Preparation of hydrogel system
[0074] 2.1. Add 24.00 g purified water to swell 0.08 g carrageenan, 0.06 g konjac glucomannan, 1.79 g polyvinyl pyrrolidone, 5.11 g gelatin, 0.05 g citric acid and 0.12 g chitosan, and heat and stir at 55° C. for 60 min to dissolve and prepare a solution to obtain the first phase;
[0075] 2.2. Dissolve 30.00 g of glycerol, 23.00 g of sodium polyacrylate and 9.00 g of kaolin at room temperature and stir for 15 min to obtain the second phase;
[0076] 3. Mix
[0077] 3.1. Add the first phase and second phase of the oil gel and hydrogel at the same time, heat and stir at 55℃ for 10 minutes, mix evenly, and then apply, cut and package.
[0078] Example 3
[0079] Monoglyceride: 0.80g;
[0080] Ethyl cellulose: 2.73 g;
[0081] Evodia rutaecarpa oil: 10.00g;
[0082] Carrageenan: 0.15g;
[0083] Konjac glucomannan: 0.11g;
[0084] Polyvinylpyrrolidone (PVP-K30): 1.10 g;
[0085] Gelatin (freezing strength value 220:): 3.90g;
[0086] Disodium ethylenediaminetetraacetate: 0.07g;
[0087] Chitosan: 0.30g;
[0088] Purified water: 32.00 g;
[0089] Glycerol: 38.00g;
[0090] Sodium polyacrylate (molecular weight: 5×10 7 ): 24.00g;
[0091] Kaolin: 7.00 g;
[0092] 1. Preparation of oil gel system
[0093] 1.1. Mix 0.80 g monoglyceride, 2.73 g ethyl cellulose and 10.00 g Evodia rutaecarpa oil, add at 1000 r / min, and heat emulsify at 80°C for 40 min to obtain an oil gel;
[0094] 2. Preparation of hydrogel system
[0095] 2.1. Add 32.00 g purified water to 0.15 g carrageenan, 0.11 g konjac glucomannan, 1.10 g polyvinyl pyrrolidone, 3.90 g gelatin, 0.07 g disodium ethylenediaminetetraacetic acid, and 0.30 g chitosan, and then heat and stir at 50° C. for 40 min to dissolve and prepare a solution to obtain the first phase;
[0096] 2.2. Dissolve 38.00 g of glycerol, 24.00 g of sodium polyacrylate and 7.00 g of kaolin at room temperature by stirring for 10 min to obtain the second phase;
[0097] 3. Mix
[0098] 3.1. Add the first phase and second phase of the oil gel and hydrogel at the same time, heat and stir at 50℃ for 15 minutes, mix evenly, and then apply, cut and package.
[0099] Example 4
[0100] Monoglyceride: 1.70g;
[0101] Ethyl cellulose: 4.00 g;
[0102] Dried ginger oil: 12.00g;
[0103] Carrageenan: 0.21g;
[0104] Konjac glucomannan: 0.18g;
[0105] Polyvinylpyrrolidone (PVP-K90): 0.48 g;
[0106] Gelatin (freezing strength value: 210): 1.52g;
[0107] Malic acid: 0.11 g;
[0108] Protamine: 0.40g;
[0109] Purified water: 18.00 g;
[0110] Glycerol: 27.00g;
[0111] Sodium polyacrylate (molecular weight: 3×10 7 ): 16.00g;
[0112] Kaolin: 5.00 g;
[0113] 1. Preparation of oil gel system
[0114] 1.1. Mix 1.70 g of monoglyceride, 4.00 g of ethyl cellulose and 12.00 g of dried ginger oil, add them, heat emulsify at 700 r / min and 85 ° C for 40 min to obtain an oil gel;
[0115] 2. Preparation of hydrogel system
[0116] 2.1. Add 18.00 g purified water to swell 0.21 g carrageenan, 0.18 g konjac glucomannan, 0.48 g polyvinyl pyrrolidone, 1.52 g gelatin, 0.11 g malic acid, and 0.40 g protamine, and heat and stir at 40° C. for 60 min to dissolve to prepare a solution to obtain the first phase;
[0117] 2.2. Dissolve 27.00 g of glycerol, 16.00 g of sodium polyacrylate and 5.00 g of kaolin at room temperature and stir for 10 min to obtain the second phase;
[0118] 3. Mix
[0119] 3.1. Add the first phase and second phase of the oil gel and hydrogel simultaneously, heat and stir at 40℃ for 10 minutes to mix evenly, then apply, cut and package.
[0120] Example 5
[0121] Monoglyceride: 1.35g;
[0122] Ethyl cellulose: 4.60 g;
[0123] Clove oil: 14.00g;
[0124] Carrageenan: 0.22g;
[0125] Konjac glucomannan: 0.21g;
[0126] Polyvinylpyrrolidone (PVP-K30): 2.24 g;
[0127] Gelatin (freezing strength value: 200): 5.76g;
[0128] Lactic acid: 0.16g;
[0129] Tea polyphenols: 0.34g;
[0130] Purified water: 48.00g;
[0131] Glycerol: 39.00g;
[0132] Sodium polyacrylate (molecular weight: 7×10 6 ): 28.00g;
[0133] Kaolin: 10.00 g;
[0134] 1. Preparation of oil gel system
[0135] 1.1. Mix 1.35 g monoglyceride, 4.60 g ethyl cellulose and 14.00 g clove oil, add them and heat emulsify at 1100 r / min and 75 ° C for 60 min to obtain an oil gel;
[0136] 2. Preparation of hydrogel system
[0137] 2.1. Add 48.00 g purified water to 0.22 g carrageenan, 0.21 g konjac glucomannan, 2.24 g polyvinyl pyrrolidone, 5.76 g gelatin, 0.16 g lactic acid, and 0.34 g tea polyphenols, and dissolve them under heating and stirring at 60° C. for 70 min to prepare a solution to obtain the first phase;
[0138] 2.2. Dissolve 39.00 g of glycerol, 28.00 g of sodium polyacrylate and 10.00 g of kaolin at room temperature and stir for 10 min to obtain the second phase;
[0139] 3. Mix
[0140] 3.1. Add the first phase and second phase of the oil gel and hydrogel at the same time, heat and stir at 60℃ for 10 minutes to mix evenly, then apply, cut and package.
[0141] Example 6
[0142] Monoglyceride: 2.10g;
[0143] Ethyl cellulose: 3.80 g;
[0144] Atractylodes lancea oil: 16.00g;
[0145] Carrageenan: 0.17g;
[0146] Konjac glucomannan: 0.15g;
[0147] Polyvinylpyrrolidone (PVP-K90): 1.40 g;
[0148] Gelatin (freezing strength value: 260): 5.60g;
[0149] Malic acid: 0.19 g;
[0150] Potassium sorbate: 0.46 g;
[0151] Purified water: 46.00g;
[0152] Glycerol: 29.00g;
[0153] Sodium polyacrylate (molecular weight: 8×10 7 ): 19.00g;
[0154] Kaolin: 6.50 g;
[0155] 1. Preparation of oil gel system
[0156] 1.1. Mix 2.10 g of monoglyceride, 3.80 g of ethyl cellulose and 16.00 g of atractylodes oil, add them at 600 r / min, and heat emulsify at 100 ° C for 30 min to obtain an oil gel;
[0157] 2. Preparation of hydrogel system
[0158] 2.1. Add 46.00 g purified water to 0.17 g carrageenan, 0.15 g konjac glucomannan, 1.40 g polyvinyl pyrrolidone, 5.60 g gelatin, 0.19 g malic acid, and 0.46 g potassium sorbate, and then heat and stir at 45° C. for 50 min to dissolve and prepare a solution to obtain the first phase;
[0159] 2.2. Dissolve 29.00 g of glycerol, 19.00 g of sodium polyacrylate and 6.50 g of kaolin at room temperature and stir for 15 min to obtain the second phase;
[0160] 3. Mix
[0161] 3.1. Add the first phase and second phase of the oil gel and hydrogel at the same time, heat and stir at 45℃ for 10 minutes, mix evenly, and then apply, cut and package.
[0162] Comparative Example 1
[0163] Monoglyceride: 0.54g;
[0164] Ethyl cellulose: 2.45 g;
[0165] Peppermint oil: 9.60g;
[0166] Carrageenan: 0.10g;
[0167] Konjac glucomannan: 0.10g;
[0168] Polyvinylpyrrolidone (PVP-K30): 1.08 g;
[0169] Gelatin (freezing strength value: 230): 2.52g;
[0170] Tartaric acid: 0.00g;
[0171] Potassium sorbate: 0.10g;
[0172] Purified water: 30.00g;
[0173] Glycerol: 36.00g;
[0174] Sodium polyacrylate (molecular weight: 6×10 4 ): 22.00g;
[0175] Kaolin: 8.30 g;
[0176] 1. Preparation of oil gel system
[0177] 1.1. Mix 0.54 g monoglyceride, 2.45 g ethyl cellulose and 9.60 g peppermint oil, add them at 800 r / min, and heat emulsify at 70°C for 40 min to obtain an oil gel;
[0178] 2. Preparation of hydrogel system
[0179] 2.1. Add 30.00 g purified water to 0.10 g carrageenan, 0.10 g konjac glucomannan, 1.08 g polyvinyl pyrrolidone, 2.52 g gelatin, 0.00 g tartaric acid, and 0.10 g potassium sorbate, and then heat and stir at 60° C. for 40 min to dissolve and prepare a solution to obtain the first phase;
[0180] 2.2. Dissolve 36.00 g of glycerol, 22.00 g of sodium polyacrylate and 8.30 g of kaolin at room temperature and stir for 10 min to obtain the second phase;
[0181] 3. Mix
[0182] 3.1. Add the first phase and second phase of the oil gel and hydrogel at the same time, heat and stir at 60℃ for 10 minutes to mix evenly, then apply, cut and package.
[0183] That is, the molecular weight of sodium polyacrylate is 6×10 4 The other steps and conditions are the same as in Example 1.
[0184] Comparative Example 2
[0185] Monoglyceride: 0.54g;
[0186] Ethyl cellulose: 2.45 g;
[0187] Peppermint oil: 9.60g;
[0188] Carrageenan: 0.10g;
[0189] Konjac glucomannan: 0.10g;
[0190] Polyvinylpyrrolidone (PVP-K30): 1.08 g;
[0191] Gelatin (freezing strength value: 230): 2.52g;
[0192] Tartaric acid: 0.00g;
[0193] Potassium sorbate: 0.10g;
[0194] Purified water: 30.00g;
[0195] Glycerol: 36.00g;
[0196] Sodium polyacrylate (molecular weight: 4×10 6 ): 22.00g;
[0197] Kaolin: 16.00 g;
[0198] 1. Preparation of oil gel system
[0199] 1.1. Mix 0.54 g monoglyceride, 2.45 g ethyl cellulose and 9.60 g peppermint oil, add them at 800 r / min, and heat emulsify at 70°C for 40 min to obtain an oil gel;
[0200] 2. Preparation of hydrogel system
[0201] 2.1. Add 30.00 g purified water to 0.10 g carrageenan, 0.10 g konjac glucomannan, 1.08 g polyvinyl pyrrolidone, 2.52 g gelatin, 0.00 g tartaric acid, and 0.10 g potassium sorbate, and then heat and stir at 60° C. for 40 min to dissolve and prepare a solution to obtain the first phase;
[0202] 2.2. Dissolve 36.00 g of glycerol, 22.00 g of sodium polyacrylate and 16.00 g of kaolin at room temperature and stir for 10 min to obtain the second phase;
[0203] 3. Mix
[0204] 3.1. Add the first phase and second phase of the oil gel and hydrogel at the same time, heat and stir at 60℃ for 10 minutes to mix evenly, then apply, cut and package.
[0205] That is, 22.00 g of sodium polyacrylate and 16.00 g of kaolin were taken, and the weight ratio of kaolin to sodium polyacrylate was maintained at 8:11. The other steps and conditions were the same as those in Example 1.
[0206] Comparative Example 3
[0207] Monoglyceride: 0.54g;
[0208] Ethyl cellulose: 2.45 g;
[0209] Peppermint oil: 9.60g;
[0210] Carrageenan: 0.10g;
[0211] Konjac glucomannan: 0.10g;
[0212] Polyvinylpyrrolidone (PVP-K30): 3.24 g;
[0213] Gelatin (freezing strength value: 230): 0.36g;
[0214] Tartaric acid: 0.00g;
[0215] Potassium sorbate: 0.10g;
[0216] Purified water: 30.00g;
[0217] Glycerol: 36.00g;
[0218] Sodium polyacrylate (molecular weight: 4×10 6 ): 22.00g;
[0219] Kaolin: 8.30 g;
[0220] 1. Preparation of oil gel system
[0221] 1.1. Mix 0.54 g monoglyceride, 2.45 g ethyl cellulose and 9.60 g peppermint oil, add them at 800 r / min, and heat emulsify at 70°C for 40 min to obtain an oil gel;
[0222] 2. Preparation of hydrogel system
[0223] 2.1. Add 30.00 g purified water to 0.10 g carrageenan, 0.10 g konjac glucomannan, 3.24 g polyvinyl pyrrolidone, 0.36 g gelatin, 0.00 g tartaric acid, and 0.10 g potassium sorbate, and then heat and stir at 60° C. for 40 min to dissolve and prepare a solution to obtain the first phase;
[0224] 2.2. Dissolve 36.00 g of glycerol, 22.00 g of sodium polyacrylate and 8.30 g of kaolin at room temperature and stir for 10 min to obtain the second phase;
[0225] 3. Mix
[0226] 3.1. Add the first phase and second phase of the oil gel and hydrogel at the same time, heat and stir at 60℃ for 10 minutes to mix evenly, then apply, cut and package.
[0227] That is, 3.24 g of polyvinyl pyrrolidone and 0.36 g of gelatin were taken, and the weight ratio of polyvinyl pyrrolidone to gelatin was maintained at 9:1. The other steps and conditions were the same as those in Example 1.
[0228] Comparative Example 4
[0229] Monoglyceride: 2.10g;
[0230] Ethyl cellulose: 3.80 g;
[0231] Atractylodes lancea oil: 16.00g;
[0232] Carrageenan: 0.05g;
[0233] Konjac glucomannan: 0.05g;
[0234] Polyvinyl pyrrolidone (PVP-K90): 0.20 g;
[0235] Gelatin (freezing strength value: 260): 0.80;
[0236] Malic acid: 0.00g;
[0237] Potassium sorbate: 0.10g;
[0238] Purified water: 12.00 g;
[0239] Glycerol: 20.00g;
[0240] Sodium polyacrylate (molecular weight: 8×10 7 ): 14.00g;
[0241] Kaolin: 4.60 g;
[0242] 1. Preparation of oil gel system
[0243] 1.1. Mix 2.10 g of monoglyceride, 3.80 g of ethyl cellulose and 16.00 g of atractylodes oil, add them at 600 r / min, and heat emulsify at 100 ° C for 30 min to obtain an oil gel;
[0244] 2. Preparation of hydrogel system
[0245] 2.1. Add 12.00 g purified water to 0.05 g carrageenan, 0.05 g konjac glucomannan, 0.20 g polyvinyl pyrrolidone, 0.80 g gelatin, 0.00 g malic acid, and 0.10 g potassium sorbate, and then heat and stir at 45° C. for 50 min to dissolve and prepare a solution to obtain the first phase;
[0246] 2.2. Dissolve 20.00 g of glycerol, 14.00 g of sodium polyacrylate and 4.60 g of kaolin at room temperature and stir for 15 min to obtain the second phase;
[0247] 3. Mix
[0248] 3.1. Add the first phase and second phase of the oil gel and hydrogel at the same time, heat and stir at 45℃ for 10 minutes to mix evenly, then apply, cut and package.
[0249] That is, 0.05 g of carrageenan, 0.05 g of konjac glucomannan, 0.20 g of polyvinyl pyrrolidone, 0.80 g of gelatin, 0.00 g of malic acid, 0.10 g of potassium sorbate, 12.00 g of purified water, 20.00 g of glycerol, 14.00 g of sodium polyacrylate, and 4.60 g of kaolin were taken, and the weight ratio of the oil gel system to the hydrogel system was maintained at 3:7. The other steps and conditions were the same as those in Example 6.
[0250] Application Example 1
[0251] Pharmaceutical paste formula
[0252] Cinnamon: 4.0g;
[0253] Alpinia oxyphylla: 5.0g;
[0254] Psoralea corylifolia: 6.0g;
[0255] Morinda officinalis: 8.4g;
[0256] Cistanche deserticola: 6.3g;
[0257] Rehmannia root: 2.0g;
[0258] Angelica: 6.0g;
[0259] Chuanxiong: 3.0g;
[0260] Eucommia ulmoides: 6.1g;
[0261] Cornus meat: 4.9g;
[0262] Poria: 4.5g;
[0263] Cuscuta: 5.8g;
[0264] Schisandra chinensis: 3.0g;
[0265] Fennel: 4.4g;
[0266] Rosa laevigata: 3.2g;
[0267] Cataplasm base formulation
[0268] Monoglyceride: 0.54g;
[0269] Ethyl cellulose: 2.45 g;
[0270] Peppermint oil: 9.60g;
[0271] Carrageenan: 0.10g;
[0272] Konjac glucomannan: 0.10g;
[0273] Polyvinylpyrrolidone (PVP-K30): 1.08 g;
[0274] Gelatin (freezing strength value: 230): 2.52g;
[0275] Tartaric acid: 0.00g;
[0276] Potassium sorbate: 0.10g;
[0277] Purified water: 30.00g;
[0278] Glycerol: 36.00g;
[0279] Sodium polyacrylate (molecular weight: 4*106): 22.00g; Kaolin: 8.30g;
[0280] 1. Extract and refine drug paste
[0281] 1.1 Weigh the raw materials in the drug paste according to the formula, 4g of cinnamon bark, 5g of Alpinia oxyphylla, 6g of Psoralea corylifolia, 8.4g of Morinda officinalis, 6.3g of Cistanche deserticola, 2g of Angelica sinensis, 3g of Chuanxiong, 6.1g of Eucommia bark, 4.9g of Cornus officinalis, 4.5g of Poria, 5.8g of Cuscuta australis, 3g of Schisandra chinensis, 4.4g of cumin, 3.2g of Rosa laevigata, add water to the weighed drug coarse grains or pieces, decoct for 2h, add 9 times the amount of water, and decoct twice;
[0282] 1.2 Then, the extract in the above step is concentrated and then an appropriate amount of ethanol is added, the alcohol content is controlled at 55%, and the solution is allowed to stand for separation, and the obtained solution is concentrated twice to obtain a drug paste;
[0283] 2. Preparation of oil gel system
[0284] 2.1. Mix 0.54 g monoglyceride, 2.45 g ethyl cellulose and 9.60 g peppermint oil, add them at 800 r / min, and heat emulsify at 70°C for 40 min to obtain an oil gel;
[0285] 3. Preparation of hydrogel system
[0286] 3.1. Add 30.00 g purified water to 0.10 g carrageenan, 0.10 g konjac glucomannan, 1.08 g polyvinyl pyrrolidone, 2.52 g gelatin, 0.00 g tartaric acid, and 0.10 g potassium sorbate, and then heat and stir at 60° C. for 40 min to dissolve and prepare a solution to obtain the first phase;
[0287] 3.2. Dissolve 36.00 g of glycerol, 22.00 g of sodium polyacrylate and 8.30 g of kaolin at room temperature and stir for 10 min to obtain the second phase;
[0288] 4. Mix
[0289] 4.1. Take 19.90g of the prepared drug paste, add the first phase and second phase of the oil gel and hydrogel at the same time, heat and stir at 60℃ for 10min, mix evenly, apply, cut and package.
[0290] That is, a medicinal paste for warming the kidney and tonifying yang is added to the base of the cataplasm to prepare a complete cataplasm. The other steps and conditions are the same as those in Example 1.
[0291] The skin-friendly and rapidly curable dual-gel system cataplasm matrix or cataplasm samples obtained in Examples 1-6, Comparative Examples 1-4 and Application Example 1 were tested to determine the viscosity and other related physical properties as follows:
[0292] 1. Curing and molding: observe the molding time during the preparation of the cataplasm matrix or cataplasm (0-5 minutes: curing and molding time 0min-20min, 5 minutes; curing and molding time 20min-60min, 4 minutes; curing and molding time 1h-12h, 3 minutes; curing and molding time 12h-24h, 2 minutes; curing and molding time more than 24h, 0 minutes);
[0293] 2. Peelability: Take the cataplasm matrix or cataplasm sample, peel it off at 180 degrees, and observe the residue on the film (0-5 points: no residue, 5 points; severe residue, 0 point);
[0294] 3. Appearance: After removing the film, observe the matrix or surface of the cataplasm. The surface should be smooth, delicate, uniform in color, flat, free of granular micelles, bubbles, etc. (0-5 points: 5 points if it meets the above description; 0 points if it meets the above description);
[0295] 4. Stretching length: Take the cataplasm matrix or cataplasm sample, cut it into 4cm×2cm×0.2cm strips, stretch it with the same strength, and observe the stretching condition (0-5 points: stretching to 40cm and above, 5 points; stretching to 30cm-40cm, 4 points; stretching to 20cm-30cm, 3 points; stretching to 10cm-20cm, 1-2 points; stretching to less than 10cm, 0 points);
[0296] 5. Adhesion: stick the cataplasm matrix or cataplasm sample on the wrist or back, shake it back and forth 10 times, and observe the shedding condition (0-5 points: no shedding, 5 points; severe shedding, 0 points);
[0297] 6. Skin fit: Take 2 pieces of cataplasm matrix or cataplasm sample and divide them into two groups. One group is directly fitted on the artificial leather, and the other group is evenly coated with artificial sweat on the artificial leather before fitting. The two groups are hung vertically and left for a period of time to observe the shedding and skin residue (0-5 points: no shedding, no residue, 5 points; severe shedding and residue, 0 points);
[0298] 7. Excipient: Take one sheet of the cataplasm matrix or cataplasm sample on the backing, place it in a constant temperature and humidity chamber at 37°C and 64% relative humidity for 30 minutes, take it out, fix the sample on a flat steel plate with a clip, and place the plate at an angle of 60° to the horizontal plane. Leave it for 24 hours to observe whether the cream surface has flowing phenomenon (0-5 points: no flowing phenomenon, 5 points; flowing phenomenon, 0 points);
[0299] 8. Allergy test: Clean and dry the skin of the tested area and the selected area should not exceed 50mm 2 , a qualified spot test equipment with a depth of about 1mm; then put the cataplasm matrix or cataplasm sample into the small chamber of the spot tester, with a dosage of about 0.02g-0.025g; then stick the spot test tape containing the cataplasm matrix or cataplasm sample from bottom to top, stick it flat and gently press it with the palm of your hand to expel the air, and stick it for 24h-48h; after sticking, remove the spot test tape for at least 30min and observe whether there are allergic symptoms such as skin itching, redness, swelling, peeling, dryness, burning, etc. (0-5 points: no above description, 5 points; meet the above description, 0 points);
[0300] 9. Physical stability: After the cataplasm matrix or cataplasm sample is placed at room temperature for a period of time, the surface should not have obvious water loss, drying, oiliness, etc., the backing material should not penetrate, and the paste and backing material should not have any adverse conditions such as delamination (0-5 points: 5 points if it meets the above description; 0 points if it does not meet the above description);
[0301] Each of the above indicators is worth 5 points, with a total of 9 items and a total of 45 points. A total score of 40-45 is considered A-level, which is excellent; a total score of 35-40 is considered B-level, which is qualified; a total score of 0-35 is considered C-level, which is unqualified.
[0302] The comprehensive evaluation results are shown in the following table:
[0303]
[0304] Examples 1-6 performed excellently in all indicators; while Comparative Examples 1-4 could not achieve all three of curing, peeling and appearance, which further illustrates that the selection of raw material specifications and the good weight ratio relationship between the components significantly improved the curing speed and stability of the patch matrix; finally, Application Example 1 illustrates that the patch matrix of the present invention is applied to the preparation of traditional Chinese medicine patch, and the curing speed is not affected, while also performing well in all aspects.
[0305] In summary, the skin-friendly, rapidly curable dual-gel system epidermal plaster matrix provided by the present invention can meet the requirements of industrial continuous production, has moderate adhesion, is non-irritating and non-allergenic to the skin, improves skin permeability, has stable quality, and has good gel mechanical properties. It can be used to prepare various traditional Chinese medicine epidermal plasters and is easy to use and promote.
[0306] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in this field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in this technical field through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the existing technology should be within the scope of protection determined by the claims.
Claims
1. A skin-friendly, fast-curing dual-gel system cataplasm matrix, characterized in that: The dual-gel system papule matrix includes an oil gel system and a hydrogel system; the oil gel system includes monoglyceride, ethyl cellulose, and volatile oil of traditional Chinese medicine; the hydrogel system includes a first phase and a second phase; the first phase includes a toughening component A, a toughening component B, purified water, a cross-linking regulator, and an antibacterial agent; the second phase includes glycerol, sodium polyacrylate, and kaolin; the toughening component A includes any one of carrageenan and konjac glucomannan or a combination of two of them; the toughening component B includes any one of polyvinyl pyrrolidone and gelatin or a combination of two of them.
2. The skin-friendly, fast-curing dual-gel system poultice matrix according to claim 1, characterized in that: In parts by weight, the double gel system cataplasm matrix includes 0.30-2.50 parts of monoglyceride, 1.00-5.00 parts of ethyl cellulose, 6.00-18.00 parts of volatile oil of traditional Chinese medicine, 0.10-0.50 parts of toughening component A, 1.00-10.00 parts of toughening component B, 12.00-48.00 parts of purified water, 0.00-0.20 parts of cross-linking regulator, 0.10-0.50 parts of antibacterial agent, 20.00-40.00 parts of glycerol, 14.00-30.00 parts of sodium polyacrylate, and 3.00-22.00 parts of kaolin.
3. The skin-friendly, fast-curing dual-gel system poultice matrix according to claim 2, characterized in that: The volatile oil of traditional Chinese medicine includes any one or more of peppermint oil, cinnamon oil, dried ginger oil, evodia rutaecarpa oil, clove oil, schizonepeta oil and atractylodes oil.
4. The skin-friendly, fast-curing dual-gel system cataplasm matrix according to claim 2, characterized in that: The polyvinyl pyrrolidone includes polyvinyl pyrrolidone K30, polyvinyl pyrrolidone K90 or a combination of the two.
5. The skin-friendly, fast-curing dual-gel system cataplasm matrix according to claim 2, characterized in that: The cross-linking regulator includes any one of citric acid, tartaric acid, lactic acid, malic acid, and disodium ethylenediaminetetraacetate, or a combination of multiple thereof.
6. The skin-friendly, fast-curing dual-gel system poultice matrix according to claim 2, characterized in that: The antibacterial agent includes any one or more combinations of potassium sorbate, chitin, chitosan, protamine and tea polyphenols.
7. The skin-friendly, fast-curing dual-gel system cataplasm matrix according to any one of claims 2 to 6, characterized in that: In parts by weight, the double gel system cataplasm matrix includes 0.30-1.00 parts of monoglyceride, 1.50-3.50 parts of ethyl cellulose, 8.00-13.00 parts of volatile oil of traditional Chinese medicine, 0.10-0.35 parts of toughening component A, 2.00-8.00 parts of toughening component B, 24.00-37.00 parts of purified water, 0.00-0.10 parts of cross-linking regulator, 0.10-0.35 parts of antibacterial agent, 28.00-38.00 parts of glycerol, 15.00-26.00 parts of sodium polyacrylate, and 5.00-16.00 parts of kaolin.
8. A method for preparing a skin-friendly, fast curable double-gel system cataplasm matrix as described in any one of claims 1 to 7, characterized in that: The method comprises the following steps: mixing monoglyceride, ethyl cellulose and volatile oil of traditional Chinese medicine by stirring, and obtaining an oil gel system by heat emulsification; swelling toughening component A, toughening component B, cross-linking regulator and antibacterial agent with appropriate amount of purified water, and then heating and stirring to dissolve to prepare a solution to obtain a first phase; and stirring and dissolving glycerin, sodium polyacrylate and kaolin at room temperature to obtain a second phase; The oil gel, the first phase and the second phase are mixed at the same time, quickly heated and stirred to mix evenly, coated on the substrate, and then cut and packaged to obtain the product.
9. The method for preparing the skin-friendly and fast curable double gel system cataplasm matrix according to claim 8, characterized in that: The monoglyceride, ethyl cellulose and Chinese medicine volatile oil are stirred and mixed at a speed of 600-1200 r / min, and the temperature of thermal emulsification is 70-100° C. After the toughening component A, toughening component B, cross-linking regulator and antibacterial agent are swollen with purified water, they are heated and stirred at 40-60° C. to dissolve and prepare a solution to obtain the first phase; the oil gel, the first phase and the second phase are heated and stirred and mixed at 40-60° C.